Hepatitis B virus infection in Latin America: A genomic medicine approach - Roman, Sonia (Baishideng Publishing Group Inc, 2014)
Hepatitis B virus (HBV) infection is the leading cause of severe chronic liver disease. This article provides a critical view of the importance of genomic medicine for the study of HBV infection and its clinical outcomes in Latin America. Three levels of evolutionary adaptation may correlate with the clinical outcomes of HBV infection. Infections in Latin America are predominantly of genotype H in Mexico and genotype F in Central and South America; these strains have historically circulated among the indigenous population. Both genotypes appear to be linked to a benign course of disease among the native and mestizo Mexicans and native South Americans. In contrast, genotypes F, A and D are common in acute and chronic infections among mestizos with Caucasian ancestry. Hepatocellular carcinoma is rare in Mexicans, but it has been associated with genotype F1b among Argentineans. This observation illustrates the significance of ascertaining the genetic and environmental factors involved in the development of HBV-related liver disease in Latin America, which contrast with those reported in other regions of the world.